THE EFFECT OF THE DOE WEIGHT ON HER REPRODUCTIVE EFFICIENY - Mohammad Ebrahim Ahmed (University of Baghdad, College of Veterinary Medicine, 2021)
Thirty-six local dose have been used and were divided in to three groups sacording to weight, in each group twelve dose. In the first group the weights of the dose were higher than ( 2.5 kgs) and less than (3 kgs). The second groups was higher than 3 kgs) and less than (3.5 kgs). The third group was higher than (3.5 kgs) and less than (4 kgs). The aim of this study was to obtain the effect of doe weight on her reproductive efficiency (gestation period, litter size, litter weight at birth and weaning, growth rate of offspring preweaning, conception rate and preweaning mortility).